Synthesis of silver nano particles and fabrication of aqueous Ag inks for inkjet printing - Kosmala, A.; Wright, Robert V.; Zhang, Qi; Kirby, Paul B. (Elsevier Science B.V., Amsterdam., 2011)
The main problem in preparing stable and printable inks containing nanoparticles for inkjetprinting is to overcome the strong agglomeration of the particles in dispersion medium. In thisstudy, the silver particles with diameter around 50 nm were produced by a simple wet chemistrymethod. Stable aqueous printable inks were formulated by using the combination of a triblockcopolymer and high intensity focused ultrasound (HIFU). Various factors that affect the inkstability, such as, copolymer content and time of HIFU treatment, were investigated. The inkcontaining 5 wt% silver has a viscosity of about 2 mPas and surface tension 30 mN/m at 25◦C,which meet inkjet printer requirements. Such inks have been successfully printed on Al2O3ceramics and low-temperature co- fired ceramics (LTCC) and the printed films show lowresistivit